2017
DOI: 10.1097/dss.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Single Session Treatment of Rolling Acne Scars Using Tumescent Anesthesia, 20% Trichloracetic Acid Extensive Subcision, and Fractional CO2 Laser

Abstract: The combination of a trichloracetic acid 20% chemical peel, subcision, and fractional CO2 laser resurfacing combined with tumescent anesthesia is both safe and effective in the treatment of rolling acne scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…Studies that only used the PROM as an outcome measurement instrument were excluded, but study details were tabulated, per protocol. We identified 188 studies that reported treatment satisfaction as an outcome: 91 on treatment of acne 68–158 and 97 on treating acne scars (a possible sequela of acne) 159–255 . These numbers show that clinicians and researchers do consider treatment satisfaction as an important outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that only used the PROM as an outcome measurement instrument were excluded, but study details were tabulated, per protocol. We identified 188 studies that reported treatment satisfaction as an outcome: 91 on treatment of acne 68–158 and 97 on treating acne scars (a possible sequela of acne) 159–255 . These numbers show that clinicians and researchers do consider treatment satisfaction as an important outcome.…”
Section: Resultsmentioning
confidence: 99%
“…There was improvement of 2.9 on a scale of 1 to 4 and few complications; 90% of the patients were satisfied. 122 A recent systematic review concluded that there is no evidence of high quality for the various interventions proposed for the treatment of acne scars due to poor methodology, lack of statistical power, lack of standardization of efficacy data and variables evaluated before the interventions. There is moderate evidence for fillers, but there is a lack of studies with prolonged follow-up (the largest was 48 weeks) and comparative with placebo or false intervention.…”
Section: Systemic Treatmentmentioning
confidence: 99%
“… 45 Taylor et al, for instance, recently developed a novel surgical instrument consisting of a long metal rod with a “W-shaped” blunt end. 55 The sharp notches at the tip are effective at capturing the fibrotic tethers in rolling scars and severing them as the rod is advanced through the subdermal plane. 55 , 56 While this improves the overall efficacy of subcision and limits the need for multiple sessions, risk of damage to deep facial structures is higher.…”
Section: Subcisionmentioning
confidence: 99%